The semantics in GPS based mobile applications for blind users navigation outdoor - Akbar, Israh; Misman, Ahmad Fatzilah (IIUM Press, International Islamic University Malaysia, 2019)
This research is a study on improving information facilitated by common GPS based mobile application for navigation especially by the blind users. For a blind person, the main source of information is words and how to improve the effectiveness of the explanation using mobile application for them is tested in this research. The long term goal of technology is to create a movable, self-contained system that allows visually impaired people to navigate through unfamiliar environments without the assistance of guides The experiment for the research took place at MFB (Malaysian Foundation for the Blind) using existing GPS based mobile applications and the results were used to prove the hypothesis that the blind are at a considerable downside because of the absence of information and providing a detailed description of the environment could be used in the GPS navigation applications for the blind pedestrians to help them navigate independently and it would enable them to take up GPS for independent navigation in unknown environment. The information derived from the research could further help in creating and improving the semantics of the GPS based navigation technology for the blind pedestrians in an unknown environment.